Bone marrows from neuroblastoma patients: An excellent source for tumor genome analyses. Issue 3 (28th October 2014) - Abbasi, M. Reza; Rifatbegovic, Fikret; Brunner, Clemens; Ladenstein, Ruth; Ambros, Inge M.; Ambros, Peter F.
Abstract : Neuroblastoma is the most common extra‐cranial solid tumor in childhood. Presence of disseminated tumor cells (DTCs) in the bone marrow (BM) at diagnosis and at relapse is a common event in stage M neuroblastomas. Although the clinical heterogeneity of disseminated neuroblastomas is frequently associated with genomic diversity, so far, only little information exists about the genomic status of DTCs. This lack of knowledge is mainly due to the varying amount of BM infiltrating tumor cells, which is usually below 30% even at diagnosis thereby hampering systematic analyses. Thus, a valuable chance to analyze metastatic and relapse clones is, so far, completely unexploited. In this study, we show that the enrichment of tumor cells in fresh or DMSO frozen BM samples with a minimum of 0.05% or 0.1% infiltration rate, respectively, by applying magnetic bead‐based technique increased the DTC content to a sufficient level to allow SNP array analyses in 49 out of 69 samples. In addition, we successfully used non‐enriched BM samples with ≥30% DTCs including non‐stained and immunostained cytospin and BM smear slides for SNP array analyses in 44 cases. We analyzed the genomic profile of DTCs by an ultra‐high density SNP array technique with highest performance detecting all segmental chromosomal aberrations, amplified regions, acquired loss of heterozygosity events and minor aberrations affecting single genes or parts thereof. Highlights: Genomic analysis of bone marrow micrometastases by ultra‐high density SNP array. Routinely processed bone marrow (BM) samples allow detailed genomic studies. Enrichment of BM samples with >0.05% tumor cells allows detailed genomic analyses.